2022
DOI: 10.3390/su142316203
|View full text |Cite
|
Sign up to set email alerts
|

Research on Influencing Factors of Urban Road Traffic Casualties through Support Vector Machine

Abstract: Urban road traffic safety has always been vital in transportation research. This paper analyzed the factors influencing the degree of traffic accident casualties on Jinan Jingshi Road and its branch roads, taking them as the study area for urban road traffic safety problems. Additionally, it used the application of Particle Swarm Optimization (PSO), a Support Vector Machine (SVM) model, and a recursive feature elimination (RFE) to rank the contribution degree of the influencing factors. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In recent years, the rapid development an increasing scale of freeways has brought huge economic benefits to society and also provided great convenience for individuals. However, with the increase in the number of vehicles and the driving distance, freeway traffic accidents occur frequently [1,2]. Research has shown that there is a significant spatial autocorrelation between traffic accidents in various provinces and cities in China, which means that the number of traffic accidents and deaths is high with high aggregation, which leads to traffic congestion in populated areas, resulting in the waste of resources and inability to reflect sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the rapid development an increasing scale of freeways has brought huge economic benefits to society and also provided great convenience for individuals. However, with the increase in the number of vehicles and the driving distance, freeway traffic accidents occur frequently [1,2]. Research has shown that there is a significant spatial autocorrelation between traffic accidents in various provinces and cities in China, which means that the number of traffic accidents and deaths is high with high aggregation, which leads to traffic congestion in populated areas, resulting in the waste of resources and inability to reflect sustainable development.…”
Section: Introductionmentioning
confidence: 99%